The reading interests and habits of Science curriculum students and Science high school students in Quezon City - Guzman, Jamie G.
The reading interests and habits of a person can be affected by numerous factors. On this study, the socio-economic status, the extra-curricular and personal activities and the mass media are among of those many which are tested if they are contributory to the reading interests and habits of the science curriculum students and science high school students in Quezon City.